Chan Hok-lam, Legitimation in Imperial China. Discussions under the Jurchen-Chin Dynasty, Seattle, University of Wash-ington Press, 1984, xm + 267 pp. - Arsovska, Liljana (Estudios de Asia y África, 1987)
-